Pedagogical technology of developing students’ readiness for independent educational activities in the environment of digital training of professional education - Ro'ziyev Dilshod Ubaydulayevich (Global Scientific Publishing, 2024)
This article methods and means of activity of the audience in the digital educational environment , the student’s independent learning, learning and mastering under the guidance of the teacher in the process of pedagogical technology are presented
Keywords: Technology; pedagogical technology; digital education